Poultry sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
The poultry sector in the ACP varies considerably across regions and countries, ranging from small-scale production systems to large and complex commercial poultry production units. Recent years have witnessed a growing demand for poultry meat in ACP countries, where, at different levels, a series of measures are in place to strengthen the poultry sector. However, ACP producers have to cope on one hand with rising feed costs, and on the other with growing poultry imports at competitive prices. This is the case, for instance, of African imports both from Brazil (a leading poultry producer) and the EU (where a combination of internal support measures and a structured tariff regime are applied). After presenting the main 2012-13 developments of the poultry sector in the EU and in each ACP sub-region, this Executive Brief examines some of the challenges that ACP countries will have to address in the near future. It highlights the need of reconciling the interests of large-scale commercial poultry producers and small-scale producers; reconciling the interests of poultry producers with those of low-income consumers in the formulation of poultry sector trade policies; and establishing a coherent set of national and regional commercial policies, in order to avoid unfair and abusive practices in intra-regional trade.